PENGELOLAAN SAMPAH TERPADU DALAM PARIWISATA BERBASIS MASYARAKAT DI DESA BINDU, BADUNG - Sari, Putu Eka Purnama; Suryawan, Ida Bagus (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 1 (2023): Jurnal IPTA (July 2023), 2023)
Bindu Village is located in Mekar Bhuwana Village, Abiansemal, Badung Regency. The purpose of this research was to investigate the integration of waste management practices and the level of community involvement in waste management within Bindu Village. Qualitative research methodology was employed for this study, utilizing qualitative data that consisted of both primary and secondary sources. The selection of informants followed a purposive sampling technique. Qualitative descriptive analysis was utilized as the technique for analyzing the data in this study. The results of the study found that Bindu Village in managing waste has implemented integrated waste management starting from the source of waste to waste going to TPS 3R with the local community of Bindu Village having good environmental awareness with the potential to manage waste properly and correctly. However, currently the local community only follow the rules that have been made by the village regulations, there is no own initiative in planning, implementing and maintaining them.